Tropicana translated: A foreland thrust system imbricate fan setting for c. 2520 Ma orogenic gold mineralization at the northern margin of the Albany-Fraser Orogen, Western Australia - Occhipinti, S.; Tyler, I.; Spaggiari, C.; Korsch, R.; Kirkland, Chris; Smithies, R.; Martin, K.; Wingate, M. (Geological Society Publishing House, 2018)
Neoarchean rocks of the Tropicana Zone, including granites with subduction-zone affinities, formed in a terrane adjacent to, or on the margin of, the Yilgarn Craton at the commencement of a long-lived, amphibolite to granulite facies event - the 2722-2554 Ma Atlantis Event. Early stages of this event overlap with extensive komatiite emplacement within the Eastern Goldfields Superterrane (Yilgarn Craton), suggestive of a plume-related rift environment, which was followed by 2660-2630 Ma greenschist facies, orogenic gold mineralization. This indicates differences in the tectonic evolution of the Tropicana Zone compared with within the craton, although isotopic data show similarities in crustal sources. At c. 2520 Ma, the Tropicana Zone was retrogressed to greenschist facies as it was thrust onto the Yamarna Terrane (Yilgarn Craton), forming a northwesterly directed fold-and-thrust belt above the flat-lying Plumridge Detachment. This foldand- thrust belt is host to the c. 2520 Ma, Tropicana gold deposit. The Plumridge Detachment may extend north to the Yamarna greenstone belt, linking to the Yamarna Shear Zone - the boundary between the Burtville and Yamarna Terranes. The fertility of the Tropicana Zone is related to its Neoarchean geodynamic setting within a continental arc environment, implying that deformed margins of Archean cratons may be prospective for Neoarchean Au deposits.